Teaching Ethics in an Unethical World - Rehman, Sharaf N. (Annales. Etyka w Życiu Gospodarczym, 2018)
We find ourselves in times where national leaders engage in fraudulent and deceptive behaviors for personal and political gains, and multinational corporations use unethical practices to maximize their profits. Where dangerously defective products are released onto the market endangering the health and lives of consumers, and where news channels become opinion channels. Where the motto of the free market is reduced to a simple‘grab all you can, any way you can.’ In times such as these, it is difficult to teach and promote ethical behavior. A cursory look at the advertising messages and the spins put on issues by public relations people leaves one wondering if business ethics is anything more than an oxymoron – a self‑contradicting claim. In times such as ours (in 2017), it is crucial that institutions of higher learning continue to teach and foster ethical behavior and ethical responsibility. No doubt, it is an uphill struggle for educators to convince students to think and act in ethically appropriate terms when surrounded by corruption, deceit, and fraud. While no one will deny the need for ethical practices, teaching these values in a convincing manner remains a challenge. Using meta‑analysis of various University courses in ethics, the present paper attempts three goals. First, it builds a rationale for the importance of ethical behavior, the need for teaching it, and the criticisms of those who think it unnecessary to teach ethics. Second, it discusses various strategies used by universities and several educators in teaching and reinforcing ethical behavior. This section also offers a criticism of approaches and methodologies of teaching ethics. Third, it offers an outline for a syllabus for an introductory course in Ethics.